2008
DOI: 10.1177/0146167207311337
|View full text |Cite
|
Sign up to set email alerts
|

More Eyes on the Prize: Variability in White Americans' Perceptions of Progress Toward Racial Equality

Abstract: Much recent research suggests that Whites and non-Whites think differently about issues of race in contemporary America. For example, Eibach and Ehrlinger (2006) recently demonstrated that Whites perceive that more progress toward racial equality has been made as compared to non-Whites. The authors of this article sought to extend Eibach and Ehrlinger's analysis. To this end, they found that differences in Whites' and non-Whites' perceptions of racial progress can be explained by the reference points they use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…One may hypothesize that the more individuals perceive there to be great status differences in society, the more they may support programs or policies aimed at reducing this gap, such as affi rmative action or welfare. A similar analysis revealed that less perceived racial progress in the United States predicted higher support for affi rmative action policies (Brodish et al, 2008). Research has also demonstrated that, for high status group members, increased status perceptions are associated with greater amounts of ingroup bias (Federico & Levin, 2004).…”
mentioning
confidence: 89%
“…One may hypothesize that the more individuals perceive there to be great status differences in society, the more they may support programs or policies aimed at reducing this gap, such as affi rmative action or welfare. A similar analysis revealed that less perceived racial progress in the United States predicted higher support for affi rmative action policies (Brodish et al, 2008). Research has also demonstrated that, for high status group members, increased status perceptions are associated with greater amounts of ingroup bias (Federico & Levin, 2004).…”
mentioning
confidence: 89%
“…High-profile accomplishments of the American Civil Rights Movement, such as the recent election of Barack Obama as the first African-American president, often trigger concerns that public attention to these events will lead white Americans to disengage from the cause of furthering racial equality (Swarns, 2008). These concerns may be justified because research shows that white Americans tend to focus on progress toward racial equality and overlook persisting inequalities (Brodish, Brazy, & Devine, 2008;Eibach & Ehrlinger, 2006;Eibach & Keegan, 2006;Eibach & Purdie-Vaughns, 2009). Furthermore, a recent longitudinal study found that people's perceptions of racial progress increased and their support for policies to address racial inequalities decreased after Obama's election (Kaiser, Drury, Spalding, Cheryan, & O'Brien, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has documented the extensive ways that dominant and subordinate groups differ in their perspectives on social conditions (e.g., Adams et al 2006;Brodish et al 2008;Davis and Robinson 1991;Eibach and Ehrlinger 2006;Eibach and Keegan 2006;Eibach and Purdie-Vaughns 2009;Robinson 2008;Kahn et al 2009;Kluegel and Smith 1986;O'Brien et al 2009;Robinson 2008;Sidanius and Pratto 1999;Siegelman and Welch 1991). These differences in men's and women's perspectives and White and ethnic minority Americans' perspectives are so reliable and pervasive that Robinson (2008) recently described them as "perceptual segregation."…”
Section: Discussionmentioning
confidence: 99%
“…Judgments of progress toward equality tend to predict approval of policies intended to remedy inequalities. For example, the less progress White Americans believe there has been toward racial equality the more supportive they are of affirmative action for racial minorities (Brodish et al 2008). It is possible that judgments of progress toward gender equality would similarly predict people's attitudes toward policies designed to address gender inequality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation